Soybean - Recent Advances in Research and Applications 2022
DOI: 10.5772/intechopen.102639
|View full text |Cite
|
Sign up to set email alerts
|

Inoculant Formulation and Application Determine Nitrogen Availability and Water Use Efficiency in Soybean Production

Abstract: Inoculation of suitable rhizobia enhances biological nitrogen fixation in soybean production and are economically viable for use among smallholder farmers due to its low price over inorganic commercial fertilizer blends. In Mozambique, inoculants are available in liquid or solid form (powder/peat or granular). Field studies were conducted in 2017 and 2018 seasons in three agroecologies (Angonia, Nampula and Ruace) in Mozambique to evaluate the performance of inoculants when applied directly to soil and on seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…Gitonga et al (2011) also reported a higher yield between 27.8 and 39.3% of Biofix inoculated TGx 1869 and TGx 1893 promiscuous soybean over the non-promiscuous Gazelle variety at Kaguru, Meru District in Kenya. Similar results have also been documented at Ruace in Mozambique where TGx 1740-2F out-yielded Safari (Savala et al, 2022). In the same study, inoculated Safari gave more yields than TGx 1740-2F at Angonia.…”
Section: Economic Importance Of Bio-inoculants For Soybean Productionsupporting
confidence: 84%
See 2 more Smart Citations
“…Gitonga et al (2011) also reported a higher yield between 27.8 and 39.3% of Biofix inoculated TGx 1869 and TGx 1893 promiscuous soybean over the non-promiscuous Gazelle variety at Kaguru, Meru District in Kenya. Similar results have also been documented at Ruace in Mozambique where TGx 1740-2F out-yielded Safari (Savala et al, 2022). In the same study, inoculated Safari gave more yields than TGx 1740-2F at Angonia.…”
Section: Economic Importance Of Bio-inoculants For Soybean Productionsupporting
confidence: 84%
“…Nitrogen accumulated in the plant biomass at the R3 stage increased with inoculation but was distinct with bio-inoculant interaction with the soybean variety. Other studies have reported an increase in N amount accumulated in plant tissue due to inoculation (Gitonga et al, 2011;Savala et al, 2021Savala et al, , 2022Omari et al, 2022). Storm accumulated more N per ha for the Biofix, Masterfix, Nitrofix, and NitroZam, while TGx 1904-6F had more N when inoculated with N-Fixer and Soygro.…”
Section: Nodulation and Biological Nitrogen Fixationmentioning
confidence: 82%
See 1 more Smart Citation
“…Overall, the inoculations applied to the soil or seeds increased the amount of biologically fixed nitrogen. 15 In a study conducted in Brazil, seven different treatments were compared in soybean planting:…”
Section: Introductionmentioning
confidence: 99%
“…The amount of nitrogen the soybeans obtained from the atmosphere using three different inoculants was found to be 45.3%, 44.2%, and 43.6%, respectively, with yields of 2672, 1752, and 2246 kg/ha, respectively. Overall, the inoculations applied to the soil or seeds increased the amount of biologically fixed nitrogen . In a study conducted in Brazil, seven different treatments were compared in soybean planting: (1) no use of an inoculant, (2) a control group (applying 200 kg of nitrogen fertilizer/ha), (3) seed inoculation with the peat method, (4) seed inoculation with the peat method and a seed treatment with fungicide, and (5–7) the use of an inoculant inside the cultivation furrow with doses of 300, 600, and 1200 mL, in addition to a seed treatment with fungicide.…”
Section: Introductionmentioning
confidence: 99%